Mark-ups, industry structure and the business cycle - Christoph R. Weiss (Kiel University, Department of Food Economics and Consumption Studies, 1999)
Information on the primal and dual productivity measure is used to estimate industry mark-ups for 4-digit U.S. manufacturing industries. Investigating the relationship between these estimates and various industry characteristics as well as their cyclical intensive industries with high growth rates and advertising to sales ratios. In contrast to previous research we do not find significant differences in mark-ups over the business cycle. We argue that the procyclicality of margins reported in earlier studies might be caused by the (false) assumption of identical average and marginal costs.
Keywords: 330